THE BEGINNING OF MELTING OF FERTILE AND DEPLETED PERIDOTITE AT 1.5 GPA - Robinson J.A.C.; Wood B.J.; Blundy J.D. (My University, 1998)
We have determined the solidus temperatures and liquid compositions for batch melts of fertile and depleted lherzolite in the 0–15% melting interval at 1.5 GPa. Because establishment of equilibrium is difficult at very low melt fractions we have used an iterative technique in which the liquids from sandwich-type experiments are synthesized and tested for multiple saturation at the same pressure, temperature conditions as those of the sandwich experiment. Only when all 4 mantle phases are stable and of correct composition is the result accepted as being at equilibrium. This technique permits accurate determination of solidus temperatures to ±10°C and provides the compositions of low-degree mantle melts. We find that at degrees of batch melting above 3%, liquids produced from a fertile peridotite (MORB-Pyrolite) contain ∼49% SiO2, have <4% Na2O and have Fe–Mg partitioning relationships with the solid phases which are typical of basalt. As the degree of melting drops to 0% in fertile peridotite (MORB-Pyrolite), SiO2 content of the melt increases to 53% and the Na2O content to 8%. The melts remain strongly nepheline-normative and Fe favours the melt relative to olivine even more strongly than normal. We ascribe this latter observation to Na–Fe3+ coupling in the melt at high Na2O content. These high-alkali and high-silica melts are not observed at the solidus of depleted peridotite (Tinaquillo Lherzolite). These experimental results provide the first direct tests of fractional melting models which invoke the successive extraction of low-degree partial melts. No melting model currently available provides a good description of the compositions of low-degree melts from a fertile peridotite at 1.5 GPa.